Insulin-Like Peptide 3 (INSL3) Serum Concentration During Human Male Fetal Life - Harrison, Steven M.; Bush, Nicol Corbin; Wang, Yi; Mucher, Zachary R.; Lorenzo, Armando J.; Grimsby, Gwen M.; Schlomer, Bruce J.; Büllesbach, Erika E.; Baker, Linda A. (Frontiers in Endocrinology, 2019)
Context: Insulin-like peptide 3 (INSL3), a protein hormone produced by Leydig cells, may play a crucial role in testicular descent as male INSL3 knockout mice have bilateral cryptorchidism. Previous studies have measured human fetal INSL3 levels in amniotic fluid only. Objective: To measure INSL3 serum levels and mRNA in fetal umbilical cord blood and fetal testes, respectively. Design: INSL3 concentrations were assayed on 50 μl of serum from male human fetal umbilical cord blood by a non-commercial highly sensitive and specific radioimmunoassay. For secondary confirmation, quantitative real-time PCR was used to measure INSL3 relative mRNA expression in 7 age-matched human fetal testes. Setting: UT Southwestern Medical Center, Dallas, TX and Medical University of South Carolina, Charleston, SC. Patients or other Participants: Twelve human male umbilical cord blood samples and 7 human male testes were obtained from fetuses 14–21 weeks gestation. Male sex was verified by leukocyte genomic DNA SRY PCR. Interventions: None. Main Outcome Measures: Human male fetal INSL3 cord blood serum concentrations and testicular relative mRNA expression. Results: INSL3 serum concentrations during human male gestational weeks 15–20 were 2–4 times higher than published prepubertal male levels and were 5–100 times higher than previous reports of INSL3 concentrations obtained from amniotic fluid. Testicular fetal INSL3 mRNA relative expression was low from weeks 14–16, rose significantly weeks 17 and 18, and returned to low levels at week 21. Conclusions: These findings further support the role of INSL3 in human testicular descent and could prove relevant in uncovering the pathophysiology of cryptorchidism.